Updated review on novel therapies and ongoing clinical trials for high-risk non-muscle invasive bladder cancer - Brett Wiesen; Paige Hargis; Hunter Flores; Janet Kukreja (Frontiers in Oncology)
Purpose of reviewThe treatment options for high-risk non-muscle invasive bladder cancer (NMIBC), particularly in the setting of BCG-unresponsive disease, remain limited. We provide updates on recent, promising trials for high-risk NMIBC and newly FDA approved therapies.Recent findingsSeveral therapies with diverse mechanisms of action have shown favorable results in both BCG-naïve and BCG-unresponsive settings for NMIBC. These treatments include intravenous and intravesical immunotherapies, viral- and bacterial-based intravesical therapies, combination intravesical chemotherapy regimens, and novel methods of intravesical chemotherapy administration. Overall, the efficacy and tolerability of these emerging treatments for NMIBC appear promising, offering potential alternatives to radical cystectomy. There have also been recent FDA approvals for novel combination therapy for NMIBC which have been detailed below.SummaryAs the landscape of managing BCG-unresponsive disease evolves, clinical trials will continue to expand the treatment options available for NMIBC.